Peralihan Kurikulum 2013 Ke Kurikulum Merdeka Belajar Pada Mata Pelajaran Sejarah di SMA Negeri 4 Palu - Azikna Azikna; Priyatna Prasetyawati; Nuraedah Nuraedah; Wilman Darsono Lumangino (Badan Penerbit STIEPARI Press, 2025)
The formulation of the problem in this study is: (1) What are the teachers' perceptions of the transition from the independent curriculum at SMAN 4 Palu?, (2) How is the difference between the 2013 curriculum and the independent curriculum at SMAN 4 Palu? (3) What are the challenges faced by history teachers in implementing the independent learning curriculum in history subjects at SMAN 4 Palu? The objectives of this study are (1) To describe teachers' perceptions of the transition from the independent curriculum at SMAN 4 Palu, (2) To describe the differences between the 2013 curriculum and the independent curriculum at SMAN 4 Palu, (3) To describe the challenges faced by history teachers in implementing the independent learning curriculum in history subjects at SMAN 4 Palu. The type of research used is a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. Informants in this study were the Deputy Principal of Curriculum, History Teachers, and Students. The research location was at SMAN 4 Palu. The research results show that the transition from the 2013 curriculum to the independent curriculum brought positive changes. Teachers recognized significant changes in learning methods that were more inclusive, collaborative, and differentiated according to student needs. The differences between the 2013 curriculum and the independent curriculum can be seen in the simpler learning materials compared to the previous curriculum. Challenges faced by history teachers include changes in teaching paradigms, the development of teaching materials, assessment, and human resources and facilities.